Vigilant against Manipulation: The Effect of Regulatory Focus on the Use of Persuasion Knowledge - Kirmani, Amna; Zhu, Rui (Juliet) (Journal of Marketing Research, 2007)
This article proposes that compared with a promotion regulatory focus, a prevention focus increases sensitivity to the advertiser's manipulative intent. Specifically, when message cues make manipulative intent moderately salient, prevention-focused people are more likely to activate persuasion knowledge and give less favorable brand evaluations than promotion-focused people. When message cues make manipulative intent highly salient or when manipulative intent is not salient, brand evaluations do not differ across regulatory foci. In addition, externally priming suspicion of manipulative intent makes promotion-focused people react similarly to prevention-focused people, suggesting that regulatory focus affects vigilance against persuasion.